Cannabinoid potentiation of glycine receptors contributes to cannabis-induced analgesia - Xiong, Wei (2011)
Cannabinoids enhance the function of glycine receptors (GlyRs). However, little is known about the mechanisms and behavioral implication of cannabinoid-GlyR interaction. Using mutagenesis and NMR analysis, we have identified a serine at 296 in the GlyR protein critical for the potentiation of I(Gly) by Δ(9)-tetrahydrocannabinol (THC), a major psychoactive component of marijuana. The polarity of the amino acid residue at 296 and the hydroxyl groups of THC are critical for THC potentiation. Removal of the hydroxyl groups of THC results in a compound that does not affect I(Gly) when applied alone but selectively antagonizes cannabinoid-induced potentiating effect on I(Gly) and analgesic effect in a tail-flick test in mice. The cannabinoid-induced analgesia is absent in mice lacking α3GlyRs but not in those lacking CB1 and CB2 receptors. These findings reveal a new mechanism underlying cannabinoid potentiation of GlyRs, which could contribute to some of the cannabis-induced analgesic and therapeutic effects.